2020
DOI: 10.1093/ckj/sfaa032
|View full text |Cite
|
Sign up to set email alerts
|

Serum uromodulin and decline of kidney function in older participants of the population-based KORA F4/FF4 study

Abstract: Background Uromodulin, a tissue-specific tubular glycoprotein, has recently emerged as a promising biomarker for kidney function and tubular integrity. However, the association of serum uromodulin (sUmod) with renal function decline is still unknown in an older general population. Methods We analysed the association of sUmod with the estimated glomerular filtration rate (eGFR) and albuminuria in 1075 participants of the popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
3
9
0
1
Order By: Relevance
“…In the Assessment, Serial Evaluation, and Subsequent Sequelae of Acute Kidney Injury study composed of over 1500 hospitalized patients, Puthumana et al (7) showed that higher urine uromodulin levels measured after hospital discharge were associated with lower decline in eGFR and lower occurrence of CKD. Other studies have described similar relationships between serum uromodulin and kidney disease (27,28).…”
Section: Discussionsupporting
confidence: 66%
“…In the Assessment, Serial Evaluation, and Subsequent Sequelae of Acute Kidney Injury study composed of over 1500 hospitalized patients, Puthumana et al (7) showed that higher urine uromodulin levels measured after hospital discharge were associated with lower decline in eGFR and lower occurrence of CKD. Other studies have described similar relationships between serum uromodulin and kidney disease (27,28).…”
Section: Discussionsupporting
confidence: 66%
“…Continuous variables were transformed to a Gaussian distribution by the probability integral transformation followed by an inverse transform sampling and were used as in calculations per one standard deviation. In logistic and linear regression analyses, the association of sUmod with the respective dependent variables was adjusted for covariates in 5 models ( model 1 : sex, age (which are both related to hypertension and have been shown to be associated with sUmod [ 18 ]); model 2 : model 1 plus eGFR (which was decreased in hypertensive participants and is strongly related to sUmod [ 12 ]); model 3 : model 2 plus BMI (which is associated with sUmod [ 20 ]), fasting glucose (associated with sUmod [ 18 ]), current smoking, previous stroke and myocardial infarction; model 4 : model 3 plus arterial hypertension; model 5 : model 4 plus use of beta-blockers, angiotensin-converting enzyme inhibitors and angiotensin receptor antagonists, since these medications might influence the renin-aldosterone-angiotensin system). Model 1 and 2 were applied for all analyses, model 3 for the assessment of arterial hypertension, model 4 for CT-proET-1 and model 5 for renin and aldosterone as dependent variables.…”
Section: Methodsmentioning
confidence: 99%
“…SUmod is considered to reflect intact tubular cells and thus indirectly nephron mass [ 11 ]. In line, sUmod emerged as a promising marker for kidney function [ 10 , 12 , 13 ]. The physiological role of uromodulin in the systemic circulation is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…UMOD is transferred to the basolateral cell pole by a second pathway, passes the basement membrane, and enters the blood compartment in a monomeric form [19]. Patients suffering from chronic kidney disease reveal impaired biosynthesis, even in early stages where creatinine and eGFR are still within normal ranges [22][23][24][25][26]. On the other hand, patients with severe obesity may normalize deranged UMOD levels after bariatric surgery [27].…”
Section: Discussionmentioning
confidence: 99%